10 things to consider for scaling climate-smart agricultural index-based insurances - Koerner, Jana; Loboguerrero Rodriguez, Ana María (2019)
Agricultural index-based insurances can increase smallholder farmers’ resilience in a changing climate. CCAFS science successfully informs different insurance schemes around the globe. However, scaling up insurance products for the most vulnerable population remains a challenge, beyond the need to identify locally viable indices. In July 2018, CCAFS organized a South-South Cooperation event to facilitate exchange and learnings among its participants and partners, including government officials, private sector representatives and climate finance specialists and professionals. Their insights can give a first orientation to peer practitioners with plans to scale climate-smart agriculture (CSA) through insurance schemes. This Info Note is based on insights and discussions of CCAFS participants, partners and stakeholders working on climate-smart agricultural index-based insurances, during the first CCAFS South-South Collaboration Meeting in New York, July 2018.